Clinical signs as diagnostic test to assess hypoxemia in children with acute asthma exacerbation - Latifah Hanum Roni Naning Endy Paryanto Prawirohartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Asthma attack can cause hypoxemia. One of the methods to detect hypoxemia is by using pulseoximetry. However, this tool is not always available in some health care centres. Therefore, amore rapid and simple diagnostic tool is needed as an alternative method to detect hypoxemia.This study aimed to assess signs and symptoms as diagnostic tools for hypoxemia in childrenwith asthma. This was an analytical observational with cross-sectional design performed inDepartment of Pediatrics, Dr. Sardjito General Hospital/Faculty of Medicine, Universitas GadjahMada, Yogyakarta. The study was started in Februari 2010 until the sample size was sufficient.Seventy seven children with asthma between 0 – 18 years old who were presented to EmergencyDepartment and Respiratory Outpatient Clinic were involvoled in this study. All subjects wereexamined for clinical signs and oxygen saturation as the gold standard. The prevalence ofhypoxemia in children with asthma in this study was 18.2%. The best single clinical predictor ofhypoxemia was tachycardia that yielded a sensitivity of 86% (95%CI: 67 – 100%) and specificityof 59% (95%CI: 49 – 71%), and nasal flaring yielded a sensitivity of 79% and specificity of79%. The combination of 2 clinical signs namely chest wall retraction-nasal flaring increased asensitivity of 79% and specificity of 71%, chest wall retraction-tachycardia increased a sensitivityof 86% and a specificity of 76%, chest wall retraction-tachypnoe increased a sensitivity of 86%and a specificity of 51%, tachycardia-tachypnoea increased a sensitivity of 79% and a specificityof 76%. The combination 3 clinical sign namely chest wall retraction-tachycardia-tachypnoeayielded a sensitivity of 79% and specificity of 79%. In conclusion, chest wall retraction andtachycardia have higher diagnostic score than other clinical signs to assess hypoxemia in childrenwith asthma on acute exacerbation.Keywords: asthma - hypoxemia - clinical signs - children - assessment